Exporting, Wage Profiles, and Human Capital: Evidence from Brazil - Ma, Xiao; Muendler, Marc-Andreas; Nakab, Alejandro (The Review of Economics and Statistics, 2025)
Abstract Export activity shapes workers’ experience-wage profiles. Using employer-employee and customs data for Brazilian manufacturing, we document that workers’ experience-wage profiles are steeper at exporters than at non-exporters and, among exporters, steeper at exporters shipping to high-income destinations. We develop and quantify a model featuring worker-firm wage bargaining, export-market entry by multi-worker firms, and human capital accumulation by workers to interpret the data. Human capital growth can explain one-half of the differences in wage profiles between exporters and non-exporters. We show that increased human capital per worker can account for one-half of the overall gains in real income from trade openness.